Divergent urban storm response to convective, frontal and tropical systems - Xinxin Sui; John Nielsen-Gammon; Zong-Liang Yang; Dev Niyogi (Nature, 2026)
Abstract Urbanization modifies precipitation 1,2 , yet previous studies have reported inconsistent results, with some cities experiencing rainfall enhancement and others showing suppression 3 . To reconcile these discrepancies, we examine how urban impacts vary across storm types using an event-based analysis. With three-dimensional radar reflectivity data (1995–2017), we identify more than 40,000 warm-season storms across four Texas cities (Dallas, Austin, San Antonio and Houston). Here we show that classifying storms into five types reveals distinct urban influences linked to storm scales and dynamics. Local-scale single-cell and isolated storms, driven by atmospheric instability, increase in frequency (7–31%), particularly at night. Synoptic-scale frontal storms show unchanged occurrence but contrasting intensity responses: cold fronts weaken over cities by 16–28%, probably because of thermal and roughness effects, whereas warm fronts exhibit enhanced reflectivity. Tropical systems show no consistent change in frequency or intensity but exhibit a shift of high-reflectivity grid cells towards lower altitudes over urban areas. Given the diverse climate and geography of Texas, this work provides a transferable framework for understanding urban–storm interactions in other regions. These findings move beyond the traditional ‘urban wet or dry islands’ model, advancing our understanding of how urbanization modulates extreme precipitation and informing climate modelling 4,5 and resilience planning for rapidly growing cities 6,7 .